2022
DOI: 10.1093/cid/ciab1068
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tenofovir Diphosphate Levels to Predict Viremia During the Postpartum Period in Women Living With Human Immunodeficiency Virus (HIV): A Nested Case-Control Study

Abstract: Background There are few data on the utility of tenofovir diphosphate (TFV-DP) in dried blood spots to predict future viral load (VL) in postpartum women with HIV on antiretroviral therapy (ART). Methods We conducted a nested case-control study within a trial of postpartum ART delivery strategies. Participants started ART containing tenofovir disoproxil fumarate (TDF) in pregnancy, were <10 weeks postpartum and had a V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
8
2
Order By: Relevance
“…As seen in other populations [21], TFV-DP concentrations were inversely related to BMI, with lower median TFV-DP concentrations noted as BMI increased. Although other studies have established the strength of association of TFV-DP concentrations of DBS for future viremia [15,16], this study is the first to explore the association at different time-points. We showed that although both were highly predictive, a TFV-DP concentration in DBS of below 400 fmol/ punch measured 2 months prior to viral load draw had higher odds of future viral breakthough (aOR 21.3) than a drug concentration obtained 1 month prior to the viral load draw (aOR 16.1).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As seen in other populations [21], TFV-DP concentrations were inversely related to BMI, with lower median TFV-DP concentrations noted as BMI increased. Although other studies have established the strength of association of TFV-DP concentrations of DBS for future viremia [15,16], this study is the first to explore the association at different time-points. We showed that although both were highly predictive, a TFV-DP concentration in DBS of below 400 fmol/ punch measured 2 months prior to viral load draw had higher odds of future viral breakthough (aOR 21.3) than a drug concentration obtained 1 month prior to the viral load draw (aOR 16.1).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, an intervention prior to viral breakthrough could reduce the risk for patients developing antiretroviral drug resistance, and thus conserve the use of first-line single-tablet treatment regimens. To date, this predictive value has been established for TFV-DP and emtricitabine triphosphate (FTC-TP) in DBS in PWH in the United States [15] and in postpartum women in South Africa [16] but has not been assessed in a larger cohort of PWH in this setting. To address this, we present data from a longitudinal cohort of South African PWH on ART that assessed TFV-DP as a predictor of time to first viral breakthrough.…”
Section: Introductionmentioning
confidence: 99%
“…60–62 Finally, our TFV-DP thresholds were developed in persons without HIV taking PrEP, who may exhibit different pharmacokinetics compared with our population of PWLWH (as previously demonstrated). 15,17,56…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Therefore, objective and reliable tools for measuring cumulative ART adherence over time at critical points in the peripartum period are needed to improve clinical case management of peripartum WLHIV (PWLWH). 14 The quantification of tenofovir diphosphate (TFV-DP) concentrations in red blood cells using dried blood spots (DBS) is an objective assessment of cumulative (ie, longterm) drug adherence and drug exposure that is associated with viral suppression, 15 predictive of future viremia, 16,17 and reflective of improvements in adherence following behavioral interventions. 18 The long half-life of TFV-DP (17 days) in red blood cells has been translated into an adherence gradient used to estimate average TFV-DP dosing, which allows for the estimation of cumulative adherence and exposure over the preceding 6-8 weeks in people using tenofovir as part of ART or preexposure prophylaxis (PrEP) similar to the use of hemoglobin A1c in patients living with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 TFV-DP in DBS has shown to be strongly predictive of future viral breakthrough in a variety of settings and populations. [7][8][9][10][11][12][13] The clinical use of TFV-DP in managing persons with HIV (PWH) and its level of concordance with other objective measures remain understudied in RLS.…”
Section: Introductionmentioning
confidence: 99%